Reflection of Housing Names in Kazakh Language in the Linguistic Consciousness (Eurasian Journal of Philology Science and Education, 2025)
Since the emergence of humanity on Earth, housing has always been an integral part of human life and will never lose its relevance. This article examines the semantics and cultural significance of housing terminology. Housing is always considered as a reflection of the culture and social structure of society. The article compiles linguistic units related to both ancient and modern housing terms. It explores the historical and contemporary changes in housing names in the Kazakh language, as well as their representation in linguistic consciousness. The process of changing housing terms from ancient times to the present day is analyzed, along with the differences between urban and rural cultures. Housing terms in urban and rural cultures are categorized into separate groups, and the distinct features are identified. In addition, a survey was conducted among Kazakh and Kazakh-speaking respondents, and an associative analysis method was applied. The study results show that although housing names have acquired new forms and structures, their core functions remain unchanged. The study also examined outdated terms that have fallen out of use, as well as new modern housing terms that have become established in linguistic consciousness. Housing is not only an architectural art form but also a significant concept in Kazakh society, closely associated with family and daily life. Some housing terms are no longer used in the modern language and have become archaic. At the same time, the establishment of new housing terms, in line with contemporary demands was analyzed. For example, terms like penthouse, villa, and cottage are now associated with large, beautiful homes, forming clear images in people's minds. In connection with changes in civilization were systematized, and proverbs and idioms were provided to explain this process.Keywords: concept, «housing» terms, associative experiment, semantics, national consciousness, social values.